Social representations of nurses about supervision: from traditional to social - Correia, Valesca Silveira; Servo, Maria Lúcia Silva (Revista de Enfermagem UFPE on line, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> ABSTRACT Objective: to understand the representation of nurses about nursing social supervision in the family health strategy. Method: descriptive and exploratory study with qualitative approach, carried out with five nurses of family health units in Conceição do Jacuípe/BA/Brazil. The technique used for the analysis of the data was Content Analysis. The research project was approved by the the Ethics Committee of the Feira de Santana State University, with certificate CAAE 0196.0.000.059-08. Results: the study points to the possibility of development of social supervision by nurses of the family health teams when the importance of intersectoral actions is understood by re-meaning their practices aiming at the integrality of health care and the Community Health Agent is regarded as a subject involved in the process of communication in health. Conclusion: the social representations of nurses about supervision highlight the need of overcoming the traditional supervision with a new perspective of practices in health through hegemonic social supervision. Descriptors: Nursing Supervision; Family Health; Management; Representation. RESUMO Objetivo: compreender a representação das enfermeiras sobre a supervisão social em enfermagem na estratégia saúde da família. Método: estudo descritivo e exploratório, de abordagem qualitativa, realizado com cinco enfermeiras das Unidades de Saúde da Família, em Conceição do Jacuípe/BA/Brasil. Para a análise dos dados foi a Análise de Conteúdo. O projeto de pesquisa foi aprovado pelo Comitê de Ética da Universidade Estadual de Feira de Santana, com o CAAE 0196.0.000.059-08. Resultados: o estudo sinaliza a possibilidade do desenvolvimento da supervisão social pelas enfermeiras das equipes de saúde da família quando se compreende a importância das ações intersetoriais, ao resignificarem suas práticas visando a integralidade da atenção à saúde e visualizar o Agente Comunitário de Saúde como sujeito implicado no processo de comunicação em saúde. Conclusão: as representações sociais das enfermeiras sobre supervisão apontam a necessidade de superação da supervisão tradicional com um novo dimensionamento de visão das práticas em saúde de supervisão social hegemônica. Descritores: Supervisão de Enfermagem; Saúde da Família; Gerência; Representação. RESUMEN Objetivo: comprender las representaciones de enfermeras sobre supervisión social en enfermería en la estrategia de salud de la familia. Método: estudio descriptivo y exploratorio con enfoque cualitativo, realizado con cinco enfermeras de las unidades de salud de la familia en Conceição do Jacuípe/BA/Brasil. La técnica utilizada para el análisis de los datos fue el Análisis de Contenido. El proyecto de investigación fue presentado al Comité de Ética de la Universidad Estatal de Feira de Santana, y aprobado según con el certificado CAAE 0196.0.000.059-08. Resultados: el estudio señala la posibilidad de desarrollo de la supervisión social por enfermeras de los equipos de salud de la familia cuando se entiende la importancia de acciones intersectoriales al re-significar sus prácticas con objetivo de la integralidad de la atención a la salud y ver al Agente Comunitario de Salud como sujeto involucrado en el proceso de comunicación en salud. Conclusión: las representaciones sociales de las enfermeras sobre supervisión destacan la necesidad de superar la supervisión tradicional con una nueva visión de las prácticas en salud de supervisión social hegemónica. Descriptores: Supervisión de Enfermería; Salud de La Familia; Gestión; Representación.